A Delphi Survey Study to Formulate Statements on the Treatability of Inherited Metabolic Disorders to Decide on Eligibility for Newborn Screening - Abigail Veldman; M. B. Gea Kiewiet; Dineke Westra; Annet M. Bosch; Marion M. G. Brands; René I. F. M. de Coo; Terry G. J. Derks; Sabine A. Fuchs; Johanna. M. P. van den Hout; Hidde H. Huidekoper; Leo A. J. Kluijtmans; Klaas Koop; et al. (International Journal of Neonatal Screening, 2023)
The Wilson and Jungner (W&J) and Andermann criteria are meant to help select diseases eligible for population-based screening. With the introduction of next-generation sequencing (NGS) methods for newborn screening (NBS), more inherited metabolic diseases (IMDs) can technically be included, and a revision of the criteria was attempted. This study aimed to formulate statements and investigate whether those statements could elaborate on the criterion of treatability for IMDs to decide on eligibility for NBS. An online Delphi study was started among a panel of Dutch IMD experts (EPs). EPs evaluated, amended, and approved statements on treatability that were subsequently applied to 10 IMDs. After two rounds of Delphi, consensus was reached on 10 statements. Application of these statements selected 5 out of 10 IMDs proposed for this study as eligible for NBS, including 3 IMDs in the current Dutch NBS. The statement: ‘The expected benefit/burden ratio of early treatment is positive and results in a significant health outcome’ contributed most to decision-making. Our Delphi study resulted in 10 statements that can help to decide on eligibility for inclusion in NBS based on treatability, also showing that other criteria could be handled in a comparable way. Validation of the statements is required before these can be applied as guidance to authorities.